High expression of antimicrobial peptides cathelicidin-BF in Pichia pastoris and verification of its activity - Dong, Xufeng; Shan, Hu; Wang, Shubai; Jiang, Zhengjun; Wang, Shaojuan; Qin, Zhihua (Frontiers in Microbiology, 2023)
Antibacterial peptides are endogenous polypeptides produced by multicellular organisms to protect the host against pathogenic microbes, they show broad spectrum antimicrobial activities against various micro organisms and possess low propensity for developing resistance. The purpose of this study is to develop recombinant antibacterial peptide cathelicidin-BF by genetic engineering and protein engineering technology, and study its antibacterial activity in vitro and in vivo, so as to provide reference for the production and application of recombinant antibacterial peptide cathelicidin-BF. In this study, on account of Pichia pastoris eukaryotic expression system, we expressed and prepared antibacterial peptide cathelicidin-BF. Then, the minimum inhibitory concentration of antibacterial peptide cathelicidin-BF and the comparison with the antibacterial activity of antibiotics were determined through the antibacterial experiment in vitro. Chickens as infection model were used to verify the antibacterial peptide activity in vivo. The results show that the bacteriostatic ability of antibacterial peptide cathelicidin-BF is similar to that of antibiotics in certain concentration, and can reach the treatment level of antibiotics. Although the mode of administration of antibacterial peptide is still limited, this study can provide reference for the future research of antibacterial peptide.